Discovery, semisynthesis and neurite outgrowth-promoting activity of novel merrillianone/cycloparviforalone based esters as neurotrophic agents. (15th March 2021) - Wen, Tingyu; Chu, Junyan; Cheng, Wanqing; Fu, Yingying; Hu, Feixia; Yang, Ruige; Guo, Yong; Zhang, Yanbing; Liu, Jifeng
Graphical abstract: Highlights: A series of novel merrillianone/cycloparviforalone based esters were prepared. The spatial structure of compound 2h was unambiguously confirmed by X-ray crystallography. 2a, 3a and 3b exhibited about 2-fold improvement in neurite outgrowth-promoting activity compared with their precursors. Some interesting results of the structure–activity relationships (SARs) were discussed. Abstract: Natural products (NPs) are very important sources for the development of new drugs. Merrillianone and cycloparvifloralone, isolated from the roots, stems, and fruits of Illicium henryi Diels, are two natural sesquiterpene compounds. In continuation of our effort to discovery more effective neurotrophic compounds from NPs, a series of novel merrillianone/cycloparviforalone based esters 2a –i, 3a –g and 3i –q were prepared and their structures were characterized by 1 H NMR, 13 C NMR and IR spectral analyses. Furthermore, the spatial structure of compound 2h was unambiguously confirmed by X-ray crystallography. The neurite outgrowth-promoting activity results indicated that most of the target derivatives exhibited more potent neurite outgrowth-promoting activity than merrillianone and cycloparviforalone. Among all target derivatives, the neurite outgrowth-promoting activity of compounds 2a, 3a and 3b was about 2-fold stronger than that of their precursors merrillianone and cycloparviforalone, respectively. Besides, compounds 2a and 3a displayed relatively low cytotoxicity to normal GES-1 cells. Moreover, these derivatives had good hydrolytic stability. Finally, some interesting results of the structure–activity relationships (SARs) were also discussed. This work will pave the way for the development of merrillianone/cycloparviforalone derivatives as potential neurotrophic agents.